2019
DOI: 10.1177/0734242x19883921
|View full text |Cite
|
Sign up to set email alerts
|

The heavy metal leaching property and cementitious material preparation by treating municipal solid waste incineration fly ash through the molten salt process

Abstract: This research investigated the heavy metal leaching property and cementitious material preparation by treating municipal solid waste incineration fly ash through the molten salt process. The results indicated that the heavy metal thermal evaporation of fly ash in the molten salt was related to molten salt composition, heat treatment temperature and atmosphere. After treatment with sodium chloride molten salts (contains 10–50 wt% calcium chloride) from 900°C to 1000°C for 2 h, the leaching concentrations of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The treatment of FA by molten salt method could not only reduce energy consumption but also make heavy metals reach the leaching toxicity standards. And FA slag after treatment had good cementitious property (Zhao et al, 2020). Furthermore, the volatilized heavy metal chlorides could be collected for recovery and utilization, which is needed for further study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The treatment of FA by molten salt method could not only reduce energy consumption but also make heavy metals reach the leaching toxicity standards. And FA slag after treatment had good cementitious property (Zhao et al, 2020). Furthermore, the volatilized heavy metal chlorides could be collected for recovery and utilization, which is needed for further study.…”
Section: Resultsmentioning
confidence: 99%
“…The previous research showed that the optimal condition of molten salt treatment was the CaCl 2 /sodium chloride (NaCl) weight ratio 1:1, the FA/molten salt weight ratio 1:10, treatment temperature 1000°C for 2 hours in reducing atmosphere. The leaching concentration of heavy metals in FA after treatment was less than the limit value specified in GB16889-2008(Chinese Ministry of Environmental Protection, 2008, and the treated FA had good gelling properties (Zhao et al, 2020). Therefore, this experiment was carried out according to the previous conditions of molten salt treatment.…”
Section: Experiments Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that CaCl 2 and MgCl 2 first react with O 2 and/or water to generate Cl 2 and/or HCl (indirect chlorination), which are more efficacious for the majority of HMs compared to NaCl (direct chlorination). Another study also revealed that compared with the addition of NaCl alone at 900°C, adding 10% CaCl 2 to NaCl reduced the leaching concentrations of Zn, Cu, Cr, and Pb in the treated FA from 1056, 129.5, 67.6, and 1072 μg/L, respectively, to 451, 30.7, 43.9, and 177.5 μg/L, respectively, corresponding to an impressive boost in the HM volatilization rate (Zhao et al, 2020b (Yu et al, 2016). Furthermore, the volatilization of HMs in FA of low alkaline earth metals could also be amended by exerting FA of high alkaline earth metals as chlorine donor, but its effectiveness is inferior to the chlorinating agents (Yu et al, 2015a).…”
Section: Ts Technologymentioning
confidence: 95%